2005
DOI: 10.1021/om0507326
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Solution Route To Alkylated Pentalene Ligands: New Metal Monoalkylpentalenyl Complexes

Abstract: Carbene-induced rearrangement of 8,8-dibromobicyclo[5.1.0]octa-2,4-dienes and subsequent in situ deprotonation of the dihydropentalenes formed represents a straightforward and versatile solution route to pentalene ligands for use in organometallic chemistry. We report here the synthesis of 6-alkyl-substituted 8,8-dibromobicyclo[5.1.0]octa-2,4-dienes and their rearrangement to give correspondingly substituted pentalene ligands. Generation of methyl-substituted dihydropentalenes from 8,8-dibromo-6-methylbicyclo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…In complexes in which two transition metals are anchored to two cyclopentadienyl (Cp) rings, a variety of spacers connect the two Cp rings,1d, n in the most prominent of which the two rings are 1) directly linked by a σ bond (fulvalenyl);4 2) separated by saturated linkers XR 2  (X=C, Si, Ge);5 3) connected by unsaturated (CHCH) n 6 or (CC) n 7 chains (molecular wires) or arylene groups Ar;8 and 4) fused in rigid polycyclic aromatic systems (pentalene,1n, 9ac, g indacene,1n, 9dh dicyclopentanaphtalene9ik dianions, etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…In complexes in which two transition metals are anchored to two cyclopentadienyl (Cp) rings, a variety of spacers connect the two Cp rings,1d, n in the most prominent of which the two rings are 1) directly linked by a σ bond (fulvalenyl);4 2) separated by saturated linkers XR 2  (X=C, Si, Ge);5 3) connected by unsaturated (CHCH) n 6 or (CC) n 7 chains (molecular wires) or arylene groups Ar;8 and 4) fused in rigid polycyclic aromatic systems (pentalene,1n, 9ac, g indacene,1n, 9dh dicyclopentanaphtalene9ik dianions, etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al later showed TlOEt in pentane to be equally effective in generating TlPnH from H 2 Pn. 10 The first pK a of H 2 Pn must therefore be below 14, showing it to be slightly more acidic than HCp. 11 Presumably due to charge effects, deprotonation of the second ring in HPn − to furnish the fully 10π delocalised Pn 2− requires a stronger base.…”
Section: Deprotonation Of Dihydropentalenesmentioning
confidence: 98%
“…Treating the gem-dibromo cyclopropane unit in these species with methyllithium furnished 1-alkyl substituted H 2 Pn, which gave high yields of Li 2 [1-alkyl-Pn] upon double deprotonation with n butyllithium (53-70%). 10 Another synthesis of H 2 Pn via carbene rearrangement has been reported by Brinker and Fleischhauer. 29 trans-1,2-Bis(2.2dibromocyclopropyl)ethane, formed by twofold reaction of trans-1,3,5-hexatriene with CHBr 3 and KO t Bu, was found to rearrange to H 2 Pn when treated with methyllithium in diethyl ether.…”
Section: Solution-phase Rearrangement Reactionsmentioning
confidence: 99%
See 2 more Smart Citations